Sosialisasi Pemanfaatan Media Sosial Dan Internet Dalam Meningkatkan Penjualan Di SMKN 3 Kota Tangerang Selatan - Muhammad Fadli Juliana Putra; Sopyan Hidayat; Fajri Maulana Azzam Harahap; Muhammad Azriel; Tetta Thirza Herdyawan (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
In today's internet era, social media and the internet have become very potential tools for marketing, especially for students who plan to work or become young entrepreneurs. The purpose of this Community Service (PKM) activity is to teach students of SMKN 3 South Tangerang City about how to use social media and the internet to market products. This program teaches participants digital marketing strategies, creative content creation, and the use of business features on social media platforms such as Instagram, Facebook, and TikTok. The implementation method is carried out through interactive workshops, digital campaign simulations, and discussions with practitioners. The results of the activity show that students understand digital marketing better and are better at managing social media for promotion. This activity is expected to increase digital literacy and open up new economic opportunities for the younger generation when facing technology-based economic problems.